Laparoscopic management of cervical and endometrial cancer in Africa: experience of the National Hospital Centre of Pikine - Diallo, Moussa; Diouf, Abdoul Aziz; Niass, Aminata; Diallo, Astou Coly Niassy; Gombet, Cyr Esperence; Mbaye, Magatte; Biaye, Babacar; Coulbary, Sophie; Niang, Mori; Sene, Codou; Dia, Anna; Diouf, Alassane (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Laparotomy represents the standard historical surgical approach to these cancers. Process of treatment of benign adnexal pathologies to the emergence of a new pathway for the management of these cancerous pathologies. Methods: Our prospective study from December 2016 to December 2018 included 10 patients with early-stage uterine cancer and endometrial cancer confirmed by MRI. The characteristics of patients, their cancer, their intervention and morbidity were revealed. Results: Our results show that the average age of the patients was 63 years; There were 2 cases of cervical cancer and 8 cases of endometrial cancer. For cervical cancer, it was essentially squamous cell carcinoma; one patient was at stage Ia2 and the other at stage Ib1. For endometrial cancers, squamous cell carcinoma was 80%; 6 patients were in stage IB and 2 in stage IC. Of the 10 patients undergoing surgery, 9 had laparoscopic colpohysterectomy and lymphadectomy and one complementary laparoscopic lymphadenectomy. The average number of lymph nodes removed was 9 and no lymph node metastasis was found. In the immediate postoperative period, one patient had transient urinary incontinence and another had vaginal slice lymphorhea. Conclusions: The main interest of this practice is to be the least morbid possible for patients at the early stage. With our short experience, we obtained a reduction in operating time, a reduction in hospital stay, a decrease in the consumption of analgesics and antibiotics postoperatively and a reduction in per and postoperative complications.